Patient information on the internet for surgical management of inflammatory bowel disease: is it good enough? - Besson, Alex J.; Kei, Christy; Jackson, Belinda; Yeung, Trevor M.; Deftereos, Irene; Yeung, Justin M. C. (International Surgery Journal, 2020)
Background: Our study aimed to identify the search engines and terms commonly used by inflammatory bowel disease (IBD) patients and aimed to assess the quality and readability of these resources. Methods: Patients attending IBD clinic were surveyed, regarding search engines, terms and number of websites viewed. Websites according to these predetermined criteria were identified. Website content was described and quality was assessed using DISCERN. Readability was graded using the Flesch Reading Ease Score (FRES). Results: From 33 survey responses, Google was universally utilised. Forty-two websites met the inclusion criteria (19 for Crohn’s disease (CD), 23 for ulcerative colitis (UC). Only one website originated from Australia. Websites were infrequently updated (CD 21%, UC 17%) within the previous 12 months. Overall readability was poor with a mean FRES of 35.8 (11.8, range 15.7-57.7) for CD and 35.7 (11.3, range 19.4-54.3) for UC websites. Quality was moderate to poor with only five (12%) websites being rated as high quality (2 CD, 3 UC). Conclusions: There is very little Australian based web information available on IBD surgery and overall, it is of a low readability and poor content quality. There is need for the development of patient targeted health literature to help these patients.